An Adaptive Fuzzy Contrast Enhancement Algorithm with Details Preserving - Jing Rui Tang; Nor Ashidi Mat Isa (Journal of ICT Research and Applications, 2014)
This paper modifies the Adaptive Contrast Enhancement Algorithmwith Details Preserving (ACEDP) technique by integrating a fuzzy element inthe image type selection. The proposed technique, named the Adaptive FuzzyContrast Enhancement with Details Preserving (AFCEDP) technique, firstcomputes the degree of membership of the input image to three categories, i.e.low-, middle- or high-level images. The AFCEDP technique then clips thehistogram at different plateau limits that are computed from both the degree ofmembership and the clipping functions. The classification of an image in theACEDP technique is done based solely on the intensity range of the maximumnumber of pixels, which may be inaccurate. In the proposed AFCEDP technique,the image type classification is handled in a better way with the integration of afuzzy element. The performance of the proposed AFCEDP technique wascompared with the conventional ACEDP technique and several state-of-arttechniques described in the literature. The simulation results revealed that theAFCEDP technique demonstrates good capability in contrast enhancement anddetail preservation. In addition, the experiments using cervical cell images andHEp-2 cell images showed great potential of the AFCEDP technique as atechnique for enhancing medical microscopic images.